The elusive employment effect of the minimum wage - Manning, Alan (London, 2016)
"There is a huge body of empirical research on the employment effect of the minimum wage that has failed to clearly demonstrate the negative effect that so many economists strongly believe to find. This paper reviews the reasons for this and argues that the literature needs to re-focus to further our knowledge on the topic."